Incidence, persistence, and clinical relevance of iatrogenic atrial septal defects after percutaneous left atrial appendage occlusion. Issue 1 (17th December 2021) - Nelles, Dominik; Vij, Vivian; Al‐Kassou, Baravan; Weber, Marcel; Vogelhuber, Johanna; Beiert, Thomas; Nickenig, Georg; Schrickel, Jan Wilko; Sedaghat, Alexander
Abstract: Objective: To investigate the rate and clinical impact of a persisting iatrogenic atrial septal defect (iASD) after percutaneous left atrial appendage occlusion (LAAO). Background: Percutaneous LAAO is an alternative to oral anticoagulation (OAC) for the prevention of ischemic stroke and systemic embolism in patients with atrial fibrillation (AF). Data regarding incidence and persistence of iASD after LAAO procedures and its clinical relevance is scarce. Methods: We retrospectively analyzed 144 patients that underwent LAAO at our center between 2009 and 2020 who had at least one follow‐up including transesophageal echocardiography (TEE). Baseline clinical, procedural data and echocardiographic characteristics in patients with and without evidence of an iASD were compared. We furthermore determined the rate of iASD persistence over time and evaluated outcomes of patients with and without spontaneous iASD closure. Results: After a median of 92 days (IQR 75–108 days) after LAAO, 50 patients (50/144, 34.7%) showed evidence of an iASD. Patients with iASD had higher CHADS‐VASc‐scores (4.9±1.5 vs 4.2±1.2, p = 0.03), larger left atrial volumes (80.5±30.5 ml vs 67.1±19.7 ml, p = 0.01) and were more likely to have relevant mitral regurgitation (≥° II) (46.0% vs 12.3%, p = 0.001). LAAO procedures took longer (50.1±24.3 vs 41.1±17.8 min, p = 0.06) in patients with a persisting iASD. Furthermore, larger device sizes were implanted (24.3±3.4 mm vs 22.1±2.8 mm, p = 0.03). The presence of an iASD had no impact on RV dysfunction, thromboembolism or mortality. Spontaneous closure of an iASD was documented in 52.0% (26/50). Hereby, similar risk factors were identified for the persistence of an iASD in follow‐up.